Thomas Ewing family papers - Ewing, Thomas, 1789-1871.; Ewing, Hugh, 1826-1905.; Ewing, Thomas, 1829-1896.; Ewing, Thomas, 1862-1942.; Sherman, Ellen Ewing, 1824-1888.; Sherman, William T. (William Tecumseh), 1820-1891.
Correspondence, diaries, journals, writings, speeches, biographical and genealogical material, military papers, financial and legal papers, scrapbooks, printed materials, maps, photographs, and other papers concerning American political, economic, and social life. Subjects include westward expansion and frontier life, the disposal of public lands and land speculation, law and legal practice in Ohio, Ohio and national Whig politics, anti-Jacksonianism, the Bank of the United States, the organization of the U.S. Dept. of the Interior, the California gold rush, the rise of the Republican Party, sectionalism, Kansas statehood, the Washington Peace Convention (Conference Convention) of 1861, the Civil War, the assassination of Abraham Lincoln, the impeachment of Andrew Johnson, the currency question and Greenback movement, the Ohio centennial, and the development and administration of patent law in the U.S. from 1913 to 1917.
Correspondents include Philemon Beecher, Nicholas Biddle, James Gillespie Blaine, Orville Hickman Browning, Henry Clay, Thomas Corwin, John J. Crittenden, Charles B. Goddard, Horace Greeley, William Henry Harrison, Britton Armstrong Hill, Hocking H. Hunter, Reverdy Johnson, Abbott Lawrence, Abraham Lincoln, John McLean, Richard Olney, Thomas Collier Platt, Samuel C. Pomeroy, William S. Rosecrans, William Henry Seward, John Sherman, William T. Sherman, Henry Stanbery, Noah Haynes Swayne, Allen Granbery Thurman, John Tyler, Samuel Finley Vinton, and Daniel Webster.
Library of Congress Prints and Photographs Division.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Geography and Map Division.
U.S. cabinet officer and senator from Ohio. Other family members represented include his sons, Thomas (1829-1896), U.S. Army officer and congressman from Ohio, and Hugh (1826-1905), U.S. minister to Holland; his daughter and son-in-law, Ellen Ewing Sherman (1824-1888) and William T. Sherman (1820-1891), U.S. Army officer; and his grandson, Thomas Ewing (1862-1942), U.S. commissioner of patents, lawyer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beecher, Philemon, -- 1775-1839 -- Correspondence; Biddle, Nicholas, -- 1786-1844 -- Correspondence; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Browning, Orville Hickman, -- 1806-1881 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Corwin, Thomas, -- 1794-1865 -- Correspondence; Crittenden, John J. -- 1787-1863 -- Correspondence; Goddard, Charles B. -- 1796-1864 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Harrison, William Henry, -- 1773-1841 -- Correspondence; Hill, Britton Armstrong, -- 1818-1888 -- Correspondence; Hunter, Hocking H. -- Correspondence; Jackson, Andrew, -- 1767-1845.; Johnson, Andrew, -- 1808-1875 -- Impeachment; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Lawrence, Abbott, -- 1792-1855 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Lincoln, Abraham, -- 1809-1865 -- Correspondence; McLean, John, -- 1785-1861 -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Pomeroy, S. C. -- 1816-1891 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Stanbery, Henry, -- 1803-1881 -- Correspondence; Swayne, Noah Haynes, -- 1804-1884 -- Correspondence; Thurman, Allen Granbery, -- 1813-1895 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Vinton, Samuel Finley, -- 1792-1862 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Ewing family; United States. -- Department of the Interior; Bank of the United States (1816-1836); Republican Party (U.S. : 1854- ); Whig Party (U.S.); Banks and banking; Currency question -- United States; Frontier and pioneer life; Greenbacks; Land speculation -- United States; Law -- Ohio; Patent laws and legislation; Practice of law -- Ohio; Public lands -- United States; Sectionalism (United States); California -- Gold discoveries; Kansas -- Politics and government -- 1854-1861.; Ohio -- Centennial celebrations, etc; Ohio -- Politics and government; United States -- Economic policy -- To 1933.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; United States -- Social life and customs -- 19th century; West (U.S.) -- History; Cabinet officers; Senators, U.S.Congress -- Ohio